Safety knowledge and safety leadership as determinants of workers’ safety performance in the garment industry - Azza Mantasya; Sheena Ramadhia Asmara Dhani (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Safety performance reflects an organization’s capacity to prevent workplace accidents through adequate safety knowledge and effective safety leadership. In the labor-intensive garment industry, which is characterized by high ergonomic risks and intense production demands, empirical evidence on the combined effects of safety knowledge and safety leadership on workers’ safety performance remains limited. Purpose: To examine the influence of safety knowledge and safety leadership on workers’ safety performance in the garment industry in the Solo Raya region. Method: A quantitative observational design with a cross-sectional approach was employed. The sample consisted of 211 workers selected using a total sampling technique, the research instruments included questionnaires and observation sheets. Data was analyzed using logistic regression. Results: Contextual knowledge (p = 0.045; Exp(B) = 0.096) and safety controlling (p = 0.042; Exp(B) = 11.334) had a significant effect on safety compliance, while task knowledge (p = 0.036; Exp(B) = 9.398) and safety caring (p = 0.039; Exp(B) = 10.289) significant effect on safety participation. Conclusion: Strengthening workers’ safety knowledge and safety leadership practices that emphasize effective supervision and genuine care can enhance safety performance by improving safety compliance and safety participation, thereby fostering a proactive and sustainable safety culture.